2015
DOI: 10.1111/tpj.12800
|View full text |Cite
|
Sign up to set email alerts
|

Introgression browser: high‐throughput whole‐genome SNP visualization

Abstract: SUMMARYBreeding by introgressive hybridization is a pivotal strategy to broaden the genetic basis of crops. Usually, the desired traits are monitored in consecutive crossing generations by marker-assisted selection, but their analyses fail in chromosome regions where crossover recombinants are rare or not viable. Here, we present the Introgression Browser (IBROWSER), a bioinformatics tool aimed at visualizing introgressions at nucleotide or SNP (Single Nucleotide Polymorphisms) accuracy. The software selects h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 53 publications
(79 reference statements)
0
24
0
Order By: Relevance
“…4b; Supplementary Fig. 3) was calculated using a modified 26 approach with Introgression Browser (vdef67dd) and FastTree2 40 (v2.1.7). As 99.9% of the polymorphic positions in the genome are excluded by the regular method of deleting positions in which any accession presents either no sequencing coverage, MNPs, InDels or heterozygous SNPs, we decided to keep heterozygous SNPs and regions of no coverage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4b; Supplementary Fig. 3) was calculated using a modified 26 approach with Introgression Browser (vdef67dd) and FastTree2 40 (v2.1.7). As 99.9% of the polymorphic positions in the genome are excluded by the regular method of deleting positions in which any accession presents either no sequencing coverage, MNPs, InDels or heterozygous SNPs, we decided to keep heterozygous SNPs and regions of no coverage.…”
Section: Methodsmentioning
confidence: 99%
“…1), the Surinamese sample clusters near a group largely consisting of Western Guinean forest countries. Genetic distance was calculated using concatenated SNPs following a modified 26 methodology, where distances to the Surinamese sample showed that the Western Guinean forest countries were closer than Eastern countries ( Fig. 3b and Supplementary Fig.…”
mentioning
confidence: 99%
“…Given that the genomes of most donor species are poorly characterized, marker data at best allow only the position of an introgressed segment to be defined on the basis of the loss of wheat markers; they cannot determine either the size of the introduced segment or analyse its genetic content. The recently developed ‘Introgression Browser’ (Aflitos et al ., ) combines genotypic data with phylogenetic inferences to identify the origin of an introgressed segment, but to do so, a high‐quality reference sequence of the host genome is needed, along with a large set of donor sequence data. The first of these requirements is being addressed by a concerted effort to acquire a reference sequence for bread wheat (http://www.wheatgenome.org).…”
Section: Introductionmentioning
confidence: 99%
“…(A) Genetic variations available in tomato, e.g. , missense variation in vcZWL8FA [11]. (B) Genomic variations (SNP data for ZWL8FA ) mapped to the Genome Browser.…”
Section: Figmentioning
confidence: 99%